Motorization and its impact on the development of Russian cities - Yuliya А. Koleber; Elena O. Chebakova (International Journal of Advanced Studies, 2025)
Background. Currently, issues of motorization have become widespread in large cities of Russia. This is due to its rapid development and significant impact on the functioning of urban transport systems. The process of motorization is one of the factors determining the development of urban public passenger transport, the state of the environment and the economy of the city. However, the rapid development of motorization generates a number of problems of the urban environment, which directly affect the decline in the quality of life of the population and the attractiveness of the city. As a result, a study on the development of motorization in Russian cities seems relevant.